(untitled) (Nigerian Journal of Technology, 2018)
This study presents the structural reliability of CFRP shear walls subject to blast loading. The safety of a reinforced concrete shear wall, laminated with Carbon Fibre Reinforced Polymer, is modelled with a 108.9kg of Ammonium Nitrate Fuel Oil (ANFO) an explosive, with an equivalent magnitude of 87kg Trinitrotoluene (TNT). The shear performance of the laminated wall under the blast is evaluated using the First Order Reliability Method (FORM) in MATLAB environment. An increasing decline in the shear possibility of the laminated wall was observed as the standoff distance of the explosion increased, which is consistent with experimental data. http://dx.doi.org/10.4314/njt.v37i3.10